Sistem Rekomendasi Pendukung Keputusan Pemilihan Smartphone Dengan Metode Simple Additive Weighting (SAW) Berbasis Web - Suputra, I Nengah Aryadi; Kadyanan, I Gusti Agung Gede Arya (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 2 (2020): JELIKU Volume 9 No 2, November 2020, 2020)
Smartphones are already a must-have communication technology to make it easier to live your daily life. However, with so many choices can make consumers confused in determining the appropriate choice. The  Simple Additive Weighting  (SAW) method can help in the simple process that can be applied to decision-making cases such as in smartphone selection recommendations with a wide range of attributes. In the case of this study, the results were obtained that the Realme X3 Superzoom smartphone scored the highest preference with a value of 22. With this research, it is hoped that this decision support system can help potential consumers to more easily consider in the selection of smartphones that suit their wishes or needs